Prevalence of internet addiction among medical and non-medical students of International Islamic University (IIUM), Kuantan - Abdul Hadi, Azwanis; Azmi, Nurul Husna; Azmi, Fatin Nadrah; Jasmani, Norshahida; Mohd Salim, Fatin Salina; Abd. Aziz, Karimah Hanim (IIUM Press, 2022)
Internet addiction has become a serious issue in today’s world especially among college students. Studies have shown worrying prevalence of internet addiction, with most studies were done among medical students. Hence, this study aimed to elicit the prevalence and factors associated with internet addiction among medical and non-medical students of IIUM Kuantan. A total of 107 medical and 104 non-medical students of IIUM Kuantan participated in this cross-sectional study that was conducted between July and August 2019 using convenient sampling. The Internet Addiction Test (IAT) was distributed through Whatsapp® and Instagram®. Descriptive statistics were used to describe the prevalence and sociodemographic characteristics of the respondents and binary logistic regression were used to find the factors associated with internet addiction among the respondents. 67.3% of medical students and 65.4% of non-medical students were found to be moderately addicted to the internet. The significant predictors for internet addiction for medical students were age (OR 0.235 95% CI 0.068 - 0.812) and duration spent on the internet (OR 0.235 95% CI 0.068 - 0.812). For non-medical students, the significant predictors were social networking (OR 0.137 95% CI 0.003-0.636), internet TV (OR 3.574 95% CI 1.057-12.08) and duration spent on the internet (OR 0.247 95% CI 0.06-0.91). In conclusion, the prevalence of internet addiction among medical and non-medical students in IIUM, Kuantan was proven to be a concern. Active intervention such as creating awareness on healthy internet use and identification of students with problematic internet use must be considered for successful outcome.